Managing AI-Enabled Digital and Cyber-Physical Infrastructure: A Cross-Sector Review of Project Models, Governance, and Transformation Strategies - Md Mofassel Hossain (Research Parks Publishers, 2026)
The way artificial intelligence (AI) is being integrated into our digital and cyber-physical systems is truly reshaping how organisations operate across sectors such as manufacturing, healthcare, energy, transportation, and smart cities. This change is not just about improving efficiency; it’s about making more intelligent decisions, being more adaptable, and delivering innovative services. AI systems enable us to blend human skills with intelligent automation, helping optimise resources, manage risks, and streamline workflows. However, the rise of AI also brings challenges. We have to navigate ethical dilemmas, protect data privacy, address algorithmic bias, and manage the complexities that come with these technologies. To tackle these issues, it’s crucial to have governance frameworks in place that emphasise transparency, accountability, fairness, and appropriate human oversight. Successful AI implementations often come down to teamwork, focusing on the users' needs, gradually integrating new systems, and effectively managing change. On the flip side, projects can stumble when there’s a lack of alignment, weak data governance, or resistance to cultural change.